Juridical Review of Sporadic Problem Land Registration on Village Governments in Cilacap Regency - Ian Lambang Wirawan (UMPurwokerto Law Review, 2021)
For the first time, sporadic land registration at BPN must meet the applicable requirements, one of which is a dispute-free certificate. One village in Cilacap Regency refused to make a Certificate because it was an asset dispute land that an individual won based on a court decision with permanent legal force. This research is normative juridical research conducted through a literature study that examines secondary data. Based on the Regulation of the Minister of Home Affairs Number 1 of 2016 concerning Village Asset Management Article 21 Number 3, village assets can transfer ownership because of a court decision with permanent legal force. Based on this regulation, the Village Government must release these assets from the inventory list by reporting that the Regent will sign.Keywords: Land Registration, Sporadic